GAMBARAN POLA PENGGUNAAN ANTIBIOTIK PADA PASIEN COMMON COLD ANAK DI INSTALASI RAWAT JALAN RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN - Nazhipah Isnani; Muliyani Muliyani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Common cold is infection from a virus. Inflammatory mucous membranes produce a lot of mucus so that the nose becomes blocked and difficult to breathe. This study aims to determine the characteristics of the use of antibiotics for common cold child and determine to the pattern of the use antibiotic of patients in hospital outpatient installations at RSUD dr. H. Moch. Ansari Saleh Banjarmasin. This research was an observational or non-experimental study with a descriptive design, using retrospective data that was collected patient medical record data. The results of this study ware based on the characteristics of children age research subjects who are most afflicted with common cold disease from the age of 1-5 years, based on the sex of boys are more often attacked by common cold than girls, antibiotics are most commonly used in common cold patients child is second generation Cepalosporin, Cefadroxil.